Development of Design "Simulator for Active Musical Therapy" by Taking into Account the Principles of Universal Design - E. Milchakova, N.; A. Nazarova, K. (International Journal of Engineering and Technology, 2018)
The present paper describes the process of developing and creating design of the â€œSimulator for active music therapyâ€ with adaptation for blind people. Formation and improvement of the subject-spatial environment for all social groups of the population, as well as people with disabilities (HIA) is an important task of modern society. Research in the psycho-emotional state of a person allows using various methods, such as musical influence, to provide improvements and emotional regulation of a person with a disability.Â Â